Peri-operative outcomes following major surgery for head and neck cancer in the elderly: institutional audit and case–control study. Issue 8 (3rd August 2018) - Subramaniam, N; Balasubramanian, D; Rka, P; Rathod, P; Murthy, S; Vidhyadharan, S; Rajan, S; Paul, J; Thankappan, K; Iyer, S
Abstract: Objective: Elderly patients have been consistently shown to receive suboptimal therapy for cancers of the head and neck. This study was performed to determine the peri-operative outcomes of these patients and compare them with those of younger patients. Methods: In this retrospective analysis, 115 patients aged 70 years or more undergoing major surgery for head and neck cancers were matched with 115 patients aged 50–60 years, and univariate analysis was performed. Results: Elderly patients had a reduced performance status ( p < 0.001) and more co-morbid illnesses ( p = 0.007), but a comparable intra-operative course. They had a longer median hospital stay ( p = 0.016), longer intensive care unit stay ( p = 0.04), longer median tracheostomy dependence ( p = 0.04) and were more often discharged with feeding tubes ( p < 0.001). They also had a higher incidence of post-operative non-fatal cardiac events ( p = 0.045). Conclusion: Elderly patients with good performance status should receive curative-intent surgery. Although hospital stay and tube dependence are longer, morbidity and mortality are comparable with younger patients.